Intellectual Capital Memoderasi Hubungan Green Invesment Dan Green Strategic Terhadap Nilai Perusahaan - Maulana, Ingga (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2024)
This study aims to analyze the influence of green strategy, green investment, and investment performance on firm value, with intellectual capital as a moderating variable, in LQ45 companies listed on the Indonesia Stock Exchange. This research adopts a quantitative associative approach, utilizing secondary data from annual financial reports over a specific observation period. The hypotheses were tested using panel data regression analysis. The results indicate that green investment has a negative effect on firm value, while green strategy shows no significant influence. These findings suggest that companies tend to implement green investments as part of their environmental commitments, whereas green strategies are not always aimed at enhancing firm value. Additionally, intellectual capital does not moderate the relationship between green investment or green strategy and firm value. This study highlights the need for companies to optimize their environmental approaches to generate a positive impact on firm value.